Characterization of phenolic compounds, antioxidant and antibacterial potential the extract of acerola bagasse flour - Marques, Tamara Rezende; Caetano, Aline Aparecida; Rodrigues, Leonardo Milani Avelar; Simao, Anderson Assaid; Machado, Gustavo Henrique Andrade; Correa, Angelita Duarte (Acta Scientiarum. Technology, 2017)
The agro-industrial waste from fruit presents as a promising source for the extraction of active principles with biological activity. This study evaluated the antibacterial and antioxidant activities of the extract of acerola bagasse flour (ABF) and characterized phenolic compounds by high-performance liquid chromatography. The antioxidant activity was evaluated by the free-radical scavenging activity using the ABTS+ procedure and by Î²-carotene/linoleic acid system. The antibacterial activity was evaluated by agar-well diffusion method, using the microorganisms Listeria monocytogenes ATCC 19117, Escherichia coli ATCC 11229, Pseudomonas aeruginosa ATCC 15442 and Salmonella cholerasuis ATCC 6539. In ABF extract were identified phenolic compounds, in order of increasing concentration: quercetin, p-cumárico acid, gallic acid, epigallocatechin gallate, catechin, syringic acid and epicatechin. This extract showed antioxidant potential and bactericidal activity for both gram-negative and gram-positive strains, presenting potential to be used in the food industry. Â